The development of the secretaryship to the government at the Cape of Good Hope under John Montagu, 1843-1852 - Breitenbach, J J (Rhodes University, Faculty of Humanities, Department of History, 1958)
The development of the Cape Colony during the 'forties and early 'fifties last century is, indeed, a fascinating study. And as one aspect of it, a critical study analysis of the public career of John Montagu, while he was Colonial Secretary at the Cape, is of particular interest. For, by tracing the influence of his office in relation to the changing political, social and economic structures of the colony, it is hoped some contribution will be made to the knowledge of the period. Thus, the present thesis is, in part, an examination of the duties and responsibilities of the Colonial Office; but more particularly, it is an examination of how Montagu, who virtually dominated the Cape scene for almost a decade interpreted these duties and responsibilities. By concentrating, then, on his role in the civil administration and political management of colonial affairs, other aspects are revealed. The authority of the Colonial Office, which had through the years become a sort of government 'archives', was developed to such an extent, that every memorandum issued by it seems to set the tone for government policy. More. The very fact that Montagu was, time and again, left in charge of civil affairs at the Cape, while it reveals the dominant native problem and the vital question of defence, accounts also for the patenalism in government. The most important primary sources for this study have been the British Parliamentary Papers on Cape Affairs, the Cape of Good Hope Blue Books, Government House Records and the relevant minutes of the Executive and Legislative Councils. The Annual Almanacs of the Cape proved to be invaluable; they contain a wealth of information on the institutions of government, central and local, as well as the most indispensable returns for all the many services at the Cape.
Keywords: Montagu, John, 1797-1853; Montagu family; Cape of Good Hope (Colony) -- Parliament -- Legislative Council; Cape of Good Hope (South Africa) -- History; Cape of Good Hope (South Africa) -- Politics and government